Short communication: genetic variants of Sarcocystis cruzi in infected Malaysian cattle based on 18S rDNA - Ng, Y.H.; Fong, M.Y.; Subramaniam, V.; Shahari, S.; Lau, Y.L. (2015)
Sarcocystis species are pathogenic parasites that infect a wide range of animals, including cattle. A high prevalence of cattle sarcocystosis has been reported worldwide, but its status is unknown in Malaysia. This study focused on utilizing 18S rDNA to identify Sarcocystis species in Malaysian cattle and to determine their genetic variants. In this study, only Sarcocystis cruzi was detected in Malaysian cattle. The intra-species S. cruzi phylogenetic tree analysis and principal coordinate analysis (PCoA), respectively displayed two minor groups among the parasite isolates. This finding was supported by high Wright FST value (FST = 0.647). The definitive hosts (dogs) may play a fundamental role in the development of S. cruzi genetic variants. Additionally, the existence of microheterogeneity within the S. cruzi merozoites and/or distinct genetic variants arisen from independent merozoites in mature sarcocysts, possibly contributed to the existence of intra-species variations within the population. (C) 2015 Elsevier Ltd. All rights reserved.